THE FUTURE OF HOSPITALITY MARKETING - Adi Negara, Gusti Ngurah Joko (Jurnal Ekonomi dan Pariwisata, 2017)
ABSTRACT The role of marketing in the last decade was focus on product features and had little emphasis on customer service and responsible of quality only focused by production staff. Little attention or effort was made to keep them. Today, the customer is a king and satisfying customer is a top priority in every company to get and win the customers. They must provide product-service combinations with real value to customers; high service level and meet the customer needs, wants, and expectations. They must strongly focus on customer orientation. They must be expert in building customer relations, not just build products. Marketing is no longer to be viewed as a business function but rather as a philosophy in which every employee is intensely and personally interested in keeping the customer happy. Thus, it is necessity to deliver high satisfaction to customers in order to make ongoing relationship. This high satisfaction is the key to have success in future business. The goals are to deliver long-term value and make a good relationship with customers. Customer loyalty is the results of well managing of value and customer relationship marketing. Keywords: marketing, hospitality marketing, satisfaction, relationship, loyalty